Nosso corpo em movimento - Souto, Fabrícia Quirino; Silva, Laisa Fernanda Pereira da; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf